Transcription factor ART1 mediates starch hydrolysis and mycotoxin production in Fusarium graminearum and F. verticillioides. (4th December 2015) - Oh, Mira; Son, Hokyoung; Choi, Gyung Ja; Lee, Chanhui; Kim, Jin‐Cheol; Kim, Hun; Lee, Yin‐Won
Summary: Molecular mechanisms underlying the responses to environmental factors, such as nitrogen, carbon and pH, involve components that regulate the production of secondary metabolites, including mycotoxins. In this study, we identified and characterized a gene in the FGSG_02083 locus, designated as FgArt1, which was predicted to encode a Zn(II)2 Cys6 zinc finger transcription factor. An FgArt1 deletion mutant of F usarium graminearum exhibited impaired starch hydrolysis as a result of significantly reduced α‐amylase gene expression. The deletion strain was unable to produce trichothecenes and exhibited low Tri5 and Tri6 expression levels, whereas the complemented strain showed a similar ability to produce trichothecenes as the wild‐type strain. In addition, FgArt1 deletion resulted in impairment of germination in starch liquid medium and reduced pathogenicity on flowering wheat heads. To investigate the roles of the FgArt1 homologue in F . verticillioides, we deleted the FVEG_02083 gene, and the resulting strain showed defects in starch hydrolysis, similar to the FgArt1 deletion strain, and produced no detectable level of fumonisin B1 . Fum1 and Fum12 expression levels were undetectable in the deletion strain. However, when the FvArt1 ‐deleted F . verticillioides strain was complemented with FgArt1, the resulting strain was unable to recover the production of fumonisin B1, although FgArt1 expression and starch hydrolysis were induced. Thus, our results suggest that there are different regulatory pathways governed by each ART1 transcription factor in trichothecene and fumonisin biosynthesis. Taken together, we suggest that ART1 plays an important role in both trichothecene and fumonisin biosynthesis by the regulation of genes involved in starch hydrolysis.